MINAT MAHASISWA DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK DITENTUKAN OLEH PELATIHAN PROFESIONAL, LINGKUNGAN KERJA, PENGHARGAAN FINANSIAL, DAN PERTIMBANGAN PASAR - Ni Made Tia Maharani; Luh Kade Datrini (KRISNA: Kumpulan Riset Akuntansi, 2026)
The proportional ratio of public accounting professionals to the national population in Indonesia is approximately 1:1,121,792, indicating that each public accounting professional is responsible for services to more than 100,000 individuals, as compared to Malaysia which has a ratio of 1:20,141 and Singapore 1:5,562; there is volatility in the expansion of the number of public accounting professionals in Indonesia, with an annual expansion rate of 3.32% in 2023, accelerating to 8.67% in 2024, and then de-escalating to 3.46% in 2025. The objective of this study is to analyze how accounting academics' preferences in determining their professional path as public accounting professionals are influenced by professional competency training programs, workplace conditions, monetary incentives, and market dynamics factors; This study was conducted using a quantitative methodology and data obtained through a questionnaire instrument. The findings reflect that these four constructs strengthen academic preferences, so that students are more likely to choose a profession as a public accounting professional if they have deeper insight into competency training, workplace conditions, remuneration, and market dynamics, indicating that internal and external determinants are crucial in determining accounting students' professional path decisions. Keywords: Professional Training, Work Environment, Financial Rewards, Market Considerations